VARIASIPENAMBAHANEKSTRAK JAHE MERAH (Zingiber officinale var.Rubrum) TERHADAP MUTU DAN ANTIOKSIDAN BUBUK INSTAN AKAR ALANG-ALANG - Samuel '; Usman Pato; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research purposes was to evaluate of the quality and antioxidant of the instant powder of coarse grass root with the addition of red ginger extracts. The method used in this research was a Complete Random Design with 4 treatments and 4 replications. The treatments were P1 (90% coarse grass root extracts : 10% ginger extracts), P2 (80% coarse grass root extracts : 20% ginger extracts), P3 (70% coarse grass root extracts : 30% ginger extracts), P4 (60% coarse grass root extracts : 40% ginger extracts). The results show that the addition of various ginger extracts significantly influenced the total sugar content, antioxidant, descriptive value of aroma and taste of instant powder, but did not affect the moisture and ash contents, color, and texture of instant powder. The best treatment was P4 (60% coarse grass root extracts : 40%  ginger extracts) with total sugar content of 57.75%, ash content 1.48%, moisture content 1.75%, hedonic organoleptic of color 3.63, flavor 3.83, taste 3.77, texture 3.57, as well as descriptive organoleptic of color 3.27, flavor 3.97, taste 4.27, texture 3.30 and over all acceptance test 3.80.   Keyword: instant powder, quality, red ginger extracts, coarse grass root.